The Impact of non-curricular coaching in finance and marketing on final-year entrepreneurial university students in Manta, Manabí - Andrade Navarrete, Mario; Tigua Tobar, Danny (International Journal of Studies in Administrative Sciences STRATEGOS, 2026)
This study analyzes the impact of non-curricular coaching on the development of financial and marketing competencies in final-year entrepreneurial university students in Manta, Manabí. A quantitative, non-experimental, cross-sectional, and correlational-explanatory design was applied, using a structured Likert-scale survey administered to 588 students from three private universities. Descriptive statistics revealed that coaching dimensions, particularly personalized feedback and financial guidance, were rated higher than competency development levels. A structural equation model (SEM) was estimated to evaluate the relationship between variables. The results showed adequate model fit in incremental indices (CFI = 0.945; TLI = 0.920) and low residual error (SRMR = 0.030), confirming the consistency of the measurement model. The structural analysis supports that non-curricular coaching positively influences financial decision-making and entrepreneurial performance, although its impact on marketing competencies remains moderate. The findings highlight the importance of integrating structured coaching strategies into higher education to strengthen applied entrepreneurial skills.